A high-voltage generator with a VDC for TFT-LCDs - Hayashi, Kentaro; Suzuki, Yasoji; Yoshida, Masahiro; Thanachayanont, Apinunt; Imai, Shigeki (My University, 2001)
A high-voltage generator using a charge pumping circuit for TFT-LCD drivers has been already presented in IDW '99. The generator has a week point that the output voltage decreases as the driving output current increases. To solve this problem, a new high-voltage generator is proposed in this paper. The generator is composed of a charge pumping circuit and a VDC (Voltage Down Converter). The operating characteristics of the generator are also examined by using HSPICE in detail. And, it is demonstrated that the proposed generator can provide stable voltage for TFT-LCD drivers even at driving output current larger than 5mA.